Infância e direitos fundamentais: a educação infantil como forma de proteção social - Brito Neto, Galdino Toscano de (2008)
This work was to focus the child as a fundamental right, focusing on the concepts of management of the Reference Center for Education Infantil (CREI's) the city of Joao Pessoa - PB, about early childhood education as a form of social protection. The research was guided considering the early childhood education as one of the most efficient forms of social protection of the young child. The study was conducted with 15 managers of CREI's selected in view of the following criteria: diversity of geographical location of CREI; age of the manager, time of expertise in managing the Children's Education; time of expertise in management of institutions of Education Child; and training of management. All 15 subjects studied were female. With an average age of 46 years, being 14 top-level and 1 of average level. The instrument for data collection was a semi-structured interview, which included the following questions: 1) How do you see the early childhood education as a right of the child?; 2) In what ways do you consider the educational practices of care / education in the perspective of effectiveness of the rights of the child?; 3) For you to early childhood education is a form of social protection?; 4) As the early childhood education contributes to the social protection of children's rights? The interviews were recorded on digital media - MP3 then transcribed. Following the criteria for the completion of the analysis of content, according BARDIN (1997), were constructed categories of analysis: perceptions about the right of the child to kindergarten; relation care - education - effectiveness of children's rights in relation kindergarten -- effectiveness of social protection of the rights of children. Analyses indicate that early childhood education is a right of the young child in the perception of managers. This in fact shows a line between their words and what determines the Brazilian educational standardization. But still linger remnants of conceptions assistencialista that prioritize the rights of working mothers to the detriment of the rights of children. The results show the perception of early childhood education as a right justified and not guaranteed, as well as a conceptual incompleteness of the managers in that the subjects pointed standard required to provide kindergarten (State, family and society). Despite the data of the research show that the managers reported work in harmony with the relationship care / education, their speeches have dissociam contradictions that the dimensions of the relationship. The data extracted that there are ideas of managing the design of small children as being integral. Note the presence of conceptions of both early childhood education that emphasize their point care as other covering other dimensions. We constructions of wrong perceptions they attach to CREI'so power to ensure the social protection of children isolating them from the outside world, and others who emphasize the importance of interaction with the networks of integral protection of children and adolescents. Finally, this study indicates the making of searches later that address the early childhood education as one of the most efficient ways of achieving human dignity in their most varied dimensions.